1996
DOI: 10.1172/jci118706
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal basis for the gender difference in epidermal barrier formation in the fetal rat. Acceleration by estrogen and delay by testosterone.

Abstract: Previous studies have shown that ontogeny of the epidermal permeability barrier and lung occur in parallel in the fetal rat, and that pharmacologic agents, such as glucocorticoids and thyroid hormone, accelerate maturation at comparable developmental time points. Gender also influences lung maturation, i.e., males exhibit delayed development. Sex steroid hormones exert opposite effects on lung maturation, with estrogens accelerating and androgens inhibiting. In this study, we demonstrate that cutaneous barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
2
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 39 publications
7
56
2
1
Order By: Relevance
“…Although HANLEY et al [48] have reported that oestrogen accelerates and testosterone delays cutaneous barrier formation, the female smokers in this study had higher levels of serum SP-B and lower levels of CC16 than the males, suggesting worse injury despite similar cumulative smoking exposure. LANGHAMMER et al [49] have recently reported that female smokers are 50% more likely to sustain respiratory problems such as wheezing, breathlessness and asthma than male smokers.…”
Section: Pneumoproteinaemia In Smokerscontrasting
confidence: 75%
“…Although HANLEY et al [48] have reported that oestrogen accelerates and testosterone delays cutaneous barrier formation, the female smokers in this study had higher levels of serum SP-B and lower levels of CC16 than the males, suggesting worse injury despite similar cumulative smoking exposure. LANGHAMMER et al [49] have recently reported that female smokers are 50% more likely to sustain respiratory problems such as wheezing, breathlessness and asthma than male smokers.…”
Section: Pneumoproteinaemia In Smokerscontrasting
confidence: 75%
“…Unfortunately, this was not feasible since many late preterm infants especially at 35-and 36-wk gestational ages were well enough for care outside of a NICU. This investigation did not have a large enough sample size to rigorously examine other variables that may affect organ maturation such as maternal diabetes and gender (32,33). We used length of hospitalization as a proxy for resolution of clinical morbidities.…”
Section: Articlesmentioning
confidence: 99%
“…Our studies in fetal rats have shown, both in utero and in a skin explant model, that the formation of a competent barrier by day 21 of gestation coincides with the appearance of morphologically mature, extracellular lamellar membranes in the SC (7,8). Several hormones, including glucocorticoids, estrogen, and thyroid hormone, the actions of which are mediated by nuclear receptors, accelerate SC and barrier development in these models, and induce increased levels of lipid metabolic enzymes which are closely associated with barrier maturation (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%